Dynamic simulation approach for assessing green building energy performance - Ahmad Firdaus bin Ahmad Fuad (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Green Building or Green Technology is one of the Malaysian government focuses for a sustainable development by balancing economic growth and environmental sustainability. The Government recognizes green buildings contribute to sustainable development and efficient utilization of resources. At the same time, as Malaysia is still new in Green Building concept, there are only short of numbers in technical expertise and research in Building Performance Simulation using dynamic simulation especially for Green Building design. Building energy simulation is an important method to study the various energy efficiency strategies in buildings. It is one of the methods to perform building energy analysis by using a computer-based tool to simulate the energy use of a building and to quantify of the savings attributable to the proposed design. However, in many cases, architects, system designer and building owners are inexperienced with building energy modeling analysis method and lack of knowledge on how to utilize this method for decision making process in designing a building. An appropriate building energy modeling method can help to optimize the building design which allows the design team to decide the strategies, solution and investment that will give the greatest effect on the building's energy consumption. This research seeks to address the issue by developing the methodology for modeling energy use in buildings. The research methodology will utilize computer simulation to optimize and access the building design performance. Green buildings are not compulsory to have a highly technological complex system that being installed in the building, yet, its need a high level of sophistication tools in the design methodology and performance analysis in decision making process. Energy is one of the main focus in Green Building, hence, the designers need to design a building that consume less energy without compromising the occupancy comfort. By a proper method, the building energy simulation can be utilized to be an effective analytical tool for building energy research and evaluation of Green Building design. Therefore, this research will focus on Dynamic Simulation Approach for Assessing Green Building Energy Performance which is suitable for Malaysia's local climate to help in the design decision making and enhance the Green Building industry in Malaysia.